(untitled) (Medicine Today, 2013)
This is a case report of atypical pesentation of thyroid ophthalmopathy. The case report presents a patient aged 32 years with the history of oligomenorrhoea for three years , dryness and grittiness of both eye for last one year and neck swelling for six month. She was diagnosed as thyroid ophthalmopathy. The case was treated with carbimazole and improved. Early diagnosis and treatment needs for better outcome. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.16073 Medicine Today 2013 Vol.25(1): 49-51